2010
DOI: 10.1227/01.neu.0000369512.58898.99
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Case-Fatality Rates in Hospitalized Nontraumatic Subarachnoid Hemorrhage

Abstract: Case-fatality rates for hospitalized subarachnoid hemorrhages in this population-based study remained stable over 22 years, suggesting that this stroke subtype is still a very severe disease despite early management. Most deaths occurred during the first 30 days. Further work is necessary to evaluate levels of prehospital case-fatality in our population-based registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…SAH is associated with 20% to 45% mortality [134][135][136] and 10% severe disability, 136 although more comprehensive assessments demonstrate much higher rates of cognitive, social, and health disability. 137,138 SAH is not a diagnosis based on symptoms alone but rather is defined by the presence of bleeding in the subarachnoid space, confirmed by either imaging or by sampling of the CSF that occupies and circulates within the subarachnoid space.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…SAH is associated with 20% to 45% mortality [134][135][136] and 10% severe disability, 136 although more comprehensive assessments demonstrate much higher rates of cognitive, social, and health disability. 137,138 SAH is not a diagnosis based on symptoms alone but rather is defined by the presence of bleeding in the subarachnoid space, confirmed by either imaging or by sampling of the CSF that occupies and circulates within the subarachnoid space.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…2 . Approximately 12% of patients die before receiving medical attention 3 ; one month case-fatality rates for hospitalized patients range from 15-30% 4, 5 and more than one third of those who survive have major neurologic deficits 4 . Furthermore, persistent cognitive deficits are present in many survivors.…”
Section: Introductionmentioning
confidence: 99%
“…2,12,13,15,16,29,30 It has been shown that the rebleeding rate is highest on the day of the initial SAH, especially within 6 hours after onset, and it decreases steeply after 6 hours following SAH. 10,[12][13][14]17,19 Early recognition of the signs and symptoms of SAH and prompt referral to facilities where proper diagnostic and therapeutic techniques are available are essential for improvement of overall outcome.…”
mentioning
confidence: 99%